Mastering Microsoft Teams : end user guide to practical usage, collaboration, and governance - Hubbard, Melissa (Apress, 2021)
Do you need to learn how to use Microsoft Teams? Are you questioning how to drive user adoption, govern content, and manage access for your Teams deployment? Either way, the second edition of this bestseller is your one-stop-shop to learning everything you need to know to find success with Microsoft Teams. Microsoft's popular chat-based collaboration software has many rich features that enable teams to be more efficient, and save valuable time and resources. However, as with all software, there is a learning curve and pitfalls that should be avoided. Begin by learning the core components and use cases for Teams. From there, the authors guide you through ideas to create governance and adoption plans that make sense for your organization or customer. Wrap up with an understanding of features and services in progress, and a roadmap to the future of the product. What You Will Learn Implement, use, and manage Microsoft Teams Understand how Teams drives productivity and engagement by combining the functionality of Microsoft 365 Groups, SharePoint, OneDrive, Outlook, and other services in one location Govern, explain, and use Teams in your organization Use Teams in a structured way to reduce users' time spent in meetings Know the pitfalls to avoid that may create challenges in your usage of Teams Become familiar with the functionality and components of Teams via walk-throughs, including opportunities for automating business processes in Teams See how educators and students can use Teams to improve remote learning Be aware of business productivity in a remote world with Microsoft Viva This book is for anyone who wants to learn Microsoft Teams. To get the most out of the book, a basic understanding of Office 365 and a subscription, including a Microsoft Teams license, is useful.